Supply Chain Management of Sago Noodle Production in Cempaka Healthy Noodle Business - , Natelda R Timisela; , Ester D. Leatemia; , Hlouke A Huliselan (Archives of Current Research International, 2025)
The aim of this study is to determine the marketing efficiency of sago noodle product at the Cempaka Healthy Noodle business. This study employed a survey method, using critical observation to obtain detailed information on a specific problem. The survey method used a questionnaire as a data collection instrument with MSME Cempaka Healthy Noodle as the sample, selected using purposive sampling. The results showed that in the SCOR analysis, the performance value of sago Cempaka noodle supply chain was 35.430 and was included in the poor criteria. In addition, the highest and lowest weights were on the plan and source criteria, accounting for 0.386 and 0.034, respectively. The results show that there are 5 performance assessment criteria used. The highest (0.386) and lowest weight (0.034) were in plan criteria and source criteria, respectively. This shows that the plan criteria were prioritized over others. The company considered the plan criteria as important and also the basis for other processes to run according to plan.